KEBERHASILAN TRIAGE DI GAWAT DARURAT: EVALUASI KESESUAIAN KEPUTUSAN TRIAGE DENGAN KONDISI PASIEN - Heri Saepudin; Faizal Rachman; Melani Shintya Andiani; David Hadi Saputra; Rani Kusuma Ningrum; Rudy Alfonso Hutajulu (LPPM Politeknik Pajajaran ICB Bandung, 2023)
Triage aims to determine the patient's level of emergency and prioritize services based on that level of emergency. However, an inaccurate triage process can cause treatment of emergency patients to be delayed. This research was conducted using a descriptive analytical approach to evaluate the suitability of the diagnosis and determination of KSM by triage with the diagnosis and KSM actually treating patients in the emergency room at a hospital. The research results showed that 81.08% of triage diagnoses were in accordance with the diagnosis in the treatment room and 87.93% of KSM determinations by triage were in accordance with the knowledge of the specialist doctor who treated the patient. Continuous training for triage officers and monitoring and evaluation of triage protocols are needed to further improve triage accuracy.